2010
DOI: 10.1007/s11738-010-0546-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cDNAs for jasmonic acid-responsive genes in Polygonum minus roots by suppression subtractive hybridization

Abstract: Elicitation, the plant-based biotechnology approach that utilizes the ability of plant roots to absorb and secrete a vast variety of bioactive compounds, was studied on Polygonum minus using jasmonic acid (JA) as an elicitor. To understand the overall molecular responses of P. minus roots to JA induction, a subtracted cDNA library was constructed using the suppression subtractive hybridization (SSH) method. From a total of 1,344 randomly selected colonies, 190 clones were shown to be differentially expressed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 50 publications
0
10
0
2
Order By: Relevance
“…This gene was found to respond to jasmonic acid elicitation and co-up-regulated with PmADH1 and PmLOX1 upon exogenous treatment with jasmonic acid. 30,31 BLAST searches were run to nd a PmF-box1 homolog in Arabidopsis thaliana. The results returned by the BLAST search show that SKP1 interacting protein 11 (SKIP11) possesses the highest (69%) sequence similarity with PmF-box1.…”
Section: Introductionmentioning
confidence: 99%
“…This gene was found to respond to jasmonic acid elicitation and co-up-regulated with PmADH1 and PmLOX1 upon exogenous treatment with jasmonic acid. 30,31 BLAST searches were run to nd a PmF-box1 homolog in Arabidopsis thaliana. The results returned by the BLAST search show that SKP1 interacting protein 11 (SKIP11) possesses the highest (69%) sequence similarity with PmF-box1.…”
Section: Introductionmentioning
confidence: 99%
“…In the previous study, the expression of PmF-box1 was found to be increased in Persicaria minor roots after JA treatment (Gor et al 2010). Similar observations were also obtained for several other KFB proteins, such as chickpea (C. arietinum L.) grape (V. vinifera L.) and mung bean (P. vulgaris L.) (Jia et al 2011;Maldonado-Calderón et al 2011;Paquis et al 2010).…”
Section: Discussionmentioning
confidence: 83%
“…A previous study in our lab has revealed that in Persicaria minor, a gene encoding a kelch repeat containing F-box protein named PmF-box1, an ADH gene named PmADH1 and a LOX gene named PmLOX were found differentially expressed in P. minor after the plants were treated with JA (Gor et al 2010). P. minus or commonly known as kesum is very famous among Malaysians as a plant that exerts sweet and pleasant aroma.…”
Section: Introductionmentioning
confidence: 94%
“…piperis infection by suppression subtractive hybridization (SSH) (Diatchenko et al 1996), which has been used with success to identify differentially expressed genes (Aslam et al 2010;Fan et al 2010;Gor et al 2010). Our results revealed the identification of sequences coding for putative proteins related to oxidative burst and defense response processes, such as superoxide dismutase, cytochrome p450, cysteine proteinase inhibitor, and pathogenesis-related protein 4.…”
Section: Introductionmentioning
confidence: 91%